Future in the Past and Future of the Past - Zheleznyak, Olga (project baikal, 2025)
Two discourses – ‘Future in the Past’ and ‘Future of the Past’ – reveal the essence of the processes of interaction between the past, present and future, the existence of heritage, the possibility of its preservation as a system of identity, and its incorporation into contemporary life. They allow to foresee what is to be preserved, that is, the future life of heritage, and also to present art and design realities as direct ‘throws’ into the future, taking into account their ability to be constantly in the past, present and future, to be anticipation and reality at the same time.